The Effect of Training And Occupational Safety on Employee Performance in The Maliana Fire Department, Bobonaro District - Gomes, Andiano Mingos (International Journal of Economics (IJEC), 2025)
The purpose of this research is to determine how training and occupational safety influence service performance at the Corpo Bombeiru (Fire Department) institution in Maliana, Bobonaro Regency. This case study uses a quantitative approach. The data sources used in this study consisted of primary and secondary sources, with data collection techniques using questionnaires and a literature review. This study was conducted using a census method on the entire population of 42 individuals, and a sample of 30 individuals was taken using the Slovin formula. Multiple linear regression analysis was used in this study. The results showed that training and occupational safety simultaneously influenced employee performance in the Corpo Bombeiru. An R² value of 0.242 indicates that the independent variables in this study were able to explain 24.2% of the dependent variable, while the remaining 75.8% was explained by other factors not included in this study